The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1124/mol.52.5.896
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of μ-Opioid Receptor by Full but Not Partial Agonists Is Independent of G Protein Coupling

Abstract: SUMMARYIn C 6 glial cells stably expressing rat -opioid receptor, opioid agonist activation is negatively coupled to adenylyl cyclase through pertussis toxin-sensitive G proteins. H]DAMGO binding in membranes with the rank order of etorphine Ͼ DAMGO ϭ ␤-endorphin Ͼ morphine Ͼ butorphanol, and the affinity of DAMGO in alkaloid-but not peptide-treated membranes was significantly lower in comparison with control. Pertussis toxin treatment of the cells before agonist treatment did not prevent the down-regulation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 31 publications
6
47
0
Order By: Relevance
“…In contrast, PTX treatment did not have any effect on morphine-induced down-regulation of MOP in A7 cells. Yabaluri et al (Yabaluri and Medzihradsky, 1997) reported that PTX treatment did not block agonist-induced down-regulation of MOP in C6 glioma cells. However, it should be noted that PTX treatment of N2A cells expressing MOP blocked etorphine-induced MOP down-regulation (Chakrabarti, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, PTX treatment did not have any effect on morphine-induced down-regulation of MOP in A7 cells. Yabaluri et al (Yabaluri and Medzihradsky, 1997) reported that PTX treatment did not block agonist-induced down-regulation of MOP in C6 glioma cells. However, it should be noted that PTX treatment of N2A cells expressing MOP blocked etorphine-induced MOP down-regulation (Chakrabarti, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in many different cell lines demonstrated MOP down-regulation by different agonists (Baumhaker et al, 1993;Chakrabarti et al, 1995;Kato et al, 1998;Yabaluri and Medzihradsky, 1997). Chronic morphine-induced MOP down-regulation has been well investigated and characterized in a various cell culture systems, such as SH-SY5Y (Zadina et al, 1993), HEK (Onoprishvili et al, 1999), CHO (Kato et al, 1998), C6 (Yabaluri and Medzihradsky, 1997), Neuro2a (Chakrabarti et al, 1995), 7315c (only 20%) (Puttfarcken and Cox, 1989) and SK-N-SH (Baumhaker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Butorphanol pretreatment was associated with little or no tolerance development, with maximal DAMGOinduced binding of 325% above the control. Similarly, as a partial µ-opioid receptor agonist, 24-h treatment with butorphanol could reduce B max for [ by 97% from the control (45). The effects of opioid receptor binding in the whole organism are less clearly defined.…”
Section: Regulation and Trafficking Of Kormentioning
confidence: 99%
“…This agonist activity can be contrasted directly with the responses to butorphanol in C6 cells expressing the rat µ-opioid receptor (45). Treatment of such cells with the selective rat µ-opioid receptor agonist DAMGO stimulated […”
Section: Regulation and Trafficking Of Kormentioning
confidence: 99%
“…Increased in cytosolic calcium concentration activate several intracellular enzymes including protein kinases (Wroblewski and Danysz, 1989). Protein kinases such as Ca 2+ /Calmodulin-dependent protein Kinases (CaMK) have been reported to phosphorylate opioid receptor, leading to receptor desensitization (Koch et al, 1997;Mestek et al, 1995); a phenomenon which plays a critical role in opioid tolerance (Breivogel et al, 1997;Yabaluri and Medzihradsky, 1997). If this were to be the case, an essential process for opioid receptor phosphorylation and desensitization could be the activation of the Ca 2+ /calmodulin complex.…”
Section: Introductionmentioning
confidence: 99%